Media rhetoric in South Africa: a case study of the floor crossing debate - Mpokotho, Constance Sebolelo (Centre for Rhetoric Studies, 2016)
This paper makes a critical analysis of media rhetoric in South Africa. It does so by looking at the Floor Crossing Legislation debate. It makes analysis of material, and texts that were reported by different media institutions to create a particular perception by repeatedly stating the same view through different forms of communication during the floor crossing debate. It also looks at the active part that the media plays in policy formulation particularly its influence on any bill that draws significant attention. Rhetorically, the paper will look at whether the methods or arguments employed by the media were successful in manipulating public perception and presenting a particular view.